2018
DOI: 10.1080/03007995.2018.1444591
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evaluation of Hba1c, blood pressure, and weight loss among patients with type 2 diabetes mellitus treated with canagliflozin: an analysis of electronic medical records from a network of hospitals in Florida

Abstract: In CANA-treated patients and patient sub-groups from a network of Florida hospitals, improvements in quality measures and response durability were similar to clinical trials and other real-world studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The overall baseline-adjusted HbA1c reduction at 6 months (1.1%) is similar to HbA1c control reported in the meta-analysis of 38 clinical trials, 39 the recent clinical trial in 150 black patients receiving empagliflozin, 40 the US EMR-based study in 886 white and 155 black patients, 27 but lower than the average HbA1c reduction of 2.48% reported in the systematic review reported by Mazidi et al 16 However, our 6-month analysis is based on on-therapy patients, and was not an intention-to-treat analysis, and hence cannot be generalized in a real-world scenario.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The overall baseline-adjusted HbA1c reduction at 6 months (1.1%) is similar to HbA1c control reported in the meta-analysis of 38 clinical trials, 39 the recent clinical trial in 150 black patients receiving empagliflozin, 40 the US EMR-based study in 886 white and 155 black patients, 27 but lower than the average HbA1c reduction of 2.48% reported in the systematic review reported by Mazidi et al 16 However, our 6-month analysis is based on on-therapy patients, and was not an intention-to-treat analysis, and hence cannot be generalized in a real-world scenario.…”
Section: Discussionsupporting
confidence: 63%
“…38 The distributions of HbA1c, BMI and SBP in the present study were also similar to those reported in a study based on 1259 US patients treated with canagliflozin. 27 While the overall adjusted mean reduction in HbA1c at 6 months among those with HbA1c >58.5 mmol / mol% at baseline was similar in the two ethnic groups (1.1%), both ethnic groups had a mean HbA1c >63.9 mmol /mol over the 24 months after SGLT2 inhibitor initiation (similar for patients with and without ASCVD). However, black patients had a significantly higher HbA1c (on average above 69.4 mmol /mol%; Figures 1 and S2) with 33% less likelihood of achieving sustainable glycaemic control compared to white patients.…”
Section: Triglyceridesmentioning
confidence: 79%
See 1 more Smart Citation
“…These publications contain detailed information on patient characteristics, prescription orders, laboratory results, adverse effects (AEs), and withdrawals (WDs). We have identified several of these studies with canagliflozin, most of which are retrospective [ 29 , 30 , 31 ], except the Canadian Canagliflozin Registry, which was a national prospective study [ 32 ]. In all these reports, real-life effectiveness with both doses of canagliflozin (100 and 300 mg) was similar to those seen in RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…The development of DM is associated with lifestyle changes, environmental changes and healthy living behaviors [2,3]. Type-2 DM is a chronic condition characterized by hyperglycemia due to the progressive loss of β cell function and insulin resistance [4]. Indonesia's ranking of DM prevalence was the 5th in Asia Pacific [5].…”
Section: Introductionmentioning
confidence: 99%